ANALYSIS OF THE URGENCY OF MINIMUM EDUCATION STANDARDS FOR LEGISLATIVE CANDIDATES IN ELECTION IN ENSURING THE QUALITY OF LEGISLATION IN INDONESIA - Iman Sejati Zendrato; Tamaulina Br. Sembiring (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Education plays a crucial role in improving the quality of legislative candidates. A good quality education will equip them with knowledge, skills, and a deep understanding of various issues, as well as better analytical skills in making informed decisions for the benefit of the public. This analysis of the urgency of establishing higher minimum educational standards for legislative candidates in elections focuses on the impact on the quality of legislation in Indonesia. Currently, Law Number 7 of 2017 concerning Elections only requires a minimum education equivalent to high school for legislative candidates. However, the legislative function demands a high level of understanding of law, public policy, and government administration. This low educational standard contributes to the poor quality of legislative products produced, as evidenced by the minimal implementation of the National Legislation Program (Prolegnas) and the numerous laws that do not favor the public interest. This research uses a descriptive qualitative method with a normative juridical approach to examinelegislative candidacy regulations, as well as the relationship between the educational standards of legislative candidates and the quality of legislation in Indonesia.The study's findings indicate that improving the educational standards of legislative candidates is an urgent need for political system reform and better governance. Essentially, education is not merely a formality, but a crucial foundation for developing qualified legislative candidates capable of effectively carrying out their duties and responsibilities, as well as making positive contributions to regional and national development. Therefore, regulatory reforms related to increasing the minimum educational requirements for legislative candidates can serve as a strategic tool to ensure high-quality, professional, and open-minded legislation.